Application of copper-based core-shell material in aspect of adsorbing and enriching multi-component organic and inorganic sulfur pollutants

Through the application of CuO@Sp·SiO2 adsorbent of copper-based core-shell material, the problem of low treatment efficiency of multi-component sulfur-containing waste gas in the prior art is solved, and the efficient desulfurization effect is achieved under normal temperature and pressure, which is suitable for a variety of Types of sulfur source contaminants.

CN119318940AActive Publication Date: 2025-01-17KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411437944.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The prior art has limited the treatment efficiency and scope of application when dealing with complex multi-component sulfur-containing waste gases, especially in the removal of low-concentration sulfur-containing pollutants, and lacks comprehensive and efficient waste gas treatment technology.

Method used

The copper-based core-shell material CuO@Sp·SiO2 is used as the adsorbent, and nanoCuO is used as the core and mesoporous SiO2 is used as the shell, combining chemical adsorption and physical adsorption, and using electron-metal carrier interaction, the desulfurization efficiency of the adsorbent is significantly improved. And the service life of the catalyst is extended through specific preparation methods and conditions.

Benefits of technology

It has achieved efficient adsorption and removal of multi-component and single-component sulfur-containing pollutants, has good application prospects and wide applicability, reduces operating costs, and can achieve 100% desulfurization efficiency under normal temperature and pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318940A_ABST
    Figure CN119318940A_ABST
Patent Text Reader

Abstract

The invention discloses application of a copper-based core-shell material in the aspect of adsorbing and enriching multi-component organic and inorganic sulfur pollutants, and belongs to the technical field of sulfur pollutant treatment.The preparation method comprises the following steps that nano CuO, a reducing agent, a template agent and a surfactant are dissolved in water, then a silicon source is added, stirring and roasting are conducted, and the copper-based core-shell material with the nano CuO as a core and the template agent as a shell is obtained. The invention relates to a CuO (at) Sp.SiO2 adsorbent with spherical SiO2 as a shell. Wherein the mass ratio of the nano CuO to the silicon source is (0.05-0.3): 1. According to the preparation method, the CuO nano core is ingeniously wrapped in the SiO2 shell, and the core-shell CuO at Sp.SiO2 adsorbent is prepared after roasting, so that the inherent structure of the traditional adsorbent is broken through, and the desulfurization efficiency of the adsorbent is improved due to the unique interaction of the core-shell structure and the electronic metal carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sulfur pollutant treatment, and in particular relates to the application of a copper-based core-shell material in the adsorption and enrichment of multi-component organic and inorganic sulfur pollutants. Background Art

[0002] Sulfur-containing odor pollutants have a low olfactory threshold and are highly toxic. They not only pose a significant threat to human health and quality of life, but can also cause severe atmospheric pollution, such as smog. Therefore, they have become a key and difficult issue that urgently needs to be addressed in the field of environmental protection. The emission of sulfur-containing odor pollutants is also quite serious in the pulp and paper industry. Globally, the pulp and paper industry is considered one of the six most polluting industries, second only to the petroleum, cement, leather, textile, and steel industries. It has long been releasing large amounts of sulfur-containing pollutants into the natural environment. Given this, the industry urgently needs to adopt innovative and efficient environmental protection technologies.

[0003] Emissions of sulfur-containing pollutants primarily originate from the processing and use of natural wood, which releases a variety of harmful atmospheric sulfur-containing pollutants. Existing literature reports that the main components of sulfides include mercaptans and sulfide compounds, such as methyl mercaptan (CH3SH) and dimethyl disulfide (CH3SSCH3).

[0004] Current waste gas treatment technologies in the pulp and paper industry primarily include adsorption, absorption, catalytic oxidation, direct combustion, and biological treatment. These technologies often focus on removing a single pollutant. However, actual waste gas emissions often contain multiple sulfur-containing pollutants, which can interact with each other, making it difficult for a single technology to achieve optimal treatment results. Consequently, when faced with complex, multi-component sulfur-containing waste gas, existing technologies face significant limitations in both treatment efficiency and applicability.

[0005] Adsorption is widely used in industrial pollution control due to its efficient separation capabilities and relatively low operating costs. However, its application in treating waste gas containing a wide variety of sulfur pollutants is relatively limited, especially in removing low-concentration sulfur pollutants. To effectively address this challenge, the development of more comprehensive and efficient waste gas treatment technologies has become increasingly urgent. This includes developing integrated purification systems capable of simultaneously removing multiple sulfur pollutants, as well as exploring new catalysts and adsorption materials to improve treatment efficiency and reduce operating costs. Summary of the Invention

[0006] To address the above technical issues, the present invention proposes the application of a copper-based core-shell material for the adsorption and enrichment of multi-component organic and inorganic sulfur pollutants. The adsorbent obtained through the present invention's preparation method has a core-shell structure, wherein the core is macroporous CuO and the shell is mesoporous silica. The introduction of the SiO2 shell not only enables targeted adsorption of sulfur-containing atmospheres but also effectively prevents rapid deactivation of the adsorbent due to sulfur and carbon accumulation. Furthermore, the adsorbent's desulfurization efficiency is significantly improved by leveraging the strong interaction between the adsorbent's electron-metal carrier and the adsorbed species.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a core-shell CuO@Sp·SiO2 (wherein Sp represents a spherical Sphere formed during the synthesis process) adsorbent comprises the following steps:

[0009] Nano-CuO, a reducing agent, a template and a surfactant are dissolved in water, and then a silicon source is added, followed by stirring and calcination to obtain a CuO@Sp·SiO2 adsorbent with nano-CuO as the core and spherical SiO2 as the shell.

[0010] Wherein, the mass ratio of the nano-CuO to the silicon source is (0.05-0.3):1.

[0011] Beneficial Effects: CuO@Sp·SiO2's adsorption occurs primarily through a combination of chemical and physical adsorption. The nano-CuO core provides active sites, while the SiO2 shell enhances chemical stability and prevents CuO loss. Under specific conditions, the SiO2 shell can control molecular entry through its pore structure, enhancing the selective adsorption of certain target substances. When used in adsorption reactions, the catalytic activity of the nano-CuO enables more efficient reactions with reactants by increasing the contact area, while the protective effect of the SiO2 shell prolongs the catalyst's service life.

[0012] Preferably, the reducing agent comprises ethanol;

[0013] The template comprises hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride;

[0014] The surfactant is one of triethanolamine or diethanolamine;

[0015] The silicon source includes tetraethyl orthosilicate.

[0016] Beneficial Effects: As the core material, nano-CuO exhibits excellent catalytic performance and adsorption capacity, and its large surface area enables efficient adsorption of target molecules. The reducing agent, ethanol, modulates the material's electrochemical properties and adsorption capacity during the preparation process. The use of a template effectively controls the shape and thickness of the SiO2 shell, ensuring a spherical structure in the final product and improving the material's fluidity and dispersibility. Surfactants reduce surface tension, improve dispersibility, and ensure uniform bonding between the nano-CuO and SiO2, preventing aggregation and increasing the effective reaction area.

[0017] Preferably, the stirring time is 16-24 hours, and the stirring speed is 500-600 r / min.

[0018] Preferably, the conditions during the roasting process are:

[0019] Calcinate at 500-600℃ for 6-10h.

[0020] Beneficial effects: Dissolve all raw materials in water and stir thoroughly to ensure uniform mixing of the ingredients, promoting uniformity and efficiency of the reaction. The choice of calcination temperature and time is crucial and should be optimized based on the thermal stability and reaction rate of the material. For example, selecting a moderate temperature (such as 500-600°C) can effectively promote the formation of SiO2 while ensuring the stable presence of nano-CuO. The stirring speed should be adjusted to 500-600 r / min. Too fast may cause bubbles to form and affect the uniformity of deposition; too slow may lead to incomplete reaction.

[0021] Technical solution 2:

[0022] The core-shell CuO@SiO2 adsorbent was prepared by the above preparation method.

[0023] Preferably, the average diameter of the CuO@SiO2 adsorbent core is 51-52 nm, and the average diameter of the entire spherical CuO@SiO2 adsorbent is 137-138 nm.

[0024] Beneficial effects: When the material is used for adsorption reactions, the catalytic activity of nano-CuO can react more effectively with reactants by increasing the contact area, while the protective effect of the SiO2 shell can extend the service life of the catalyst.

[0025] Technical solution three:

[0026] The application of the core-shell CuO@Sp·SiO2 adsorbent in the adsorption and removal of multi-component and / or single-component sulfur-containing pollutants.

[0027] Preferably, the multi-component sulfur-containing pollutant includes three components and two components;

[0028] Among them, the three components of sulfur-containing pollutants are: CH3SH, CH3SSCH3 and H2S, and the volume ratio of the three is 3:2:7;

[0029] The two components of sulfur-containing pollutants are: CH3SH and CH3SSCH, and the volume ratio between the two is 9:1.

[0030] Preferably, the single-component sulfur-containing pollutant includes any one of CH3SH, CH3SSCH3 and H2S; more preferably H2S.

[0031] Beneficial effects: CuO@Sp·SiO2 adsorbent can efficiently adsorb multi-component and single-component sulfur-containing pollutants, showing good applicability and wide application potential, and can treat a variety of different types of sulfur sources. CH3SH: It has strong reducing properties and is widely present in natural gas and oil. Due to its strong odor, it has a significant impact on the environment. The active sites of the adsorbent contribute to its efficient removal. CH3SSCH3: As a disulfide, it has a complex structure and can be efficiently removed through appropriate adsorption mechanisms (such as chemical adsorption). H2S: It is a common and highly toxic sulfide. The use of the adsorbent of the present invention can achieve efficient removal and reduce environmental and health risks.

[0032] The fourth technical solution of the present invention:

[0033] A method for removing multi-component or single-component sulfur-containing pollutants by adsorption, comprising the following steps:

[0034] The sulfur-containing pollutant gas is introduced into a reactor containing the core-shell CuO@SiO2 adsorbent and is adsorbed and removed at room temperature, normal pressure and room temperature.

[0035] Preferably, the total sulfur concentration of the sulfur-containing pollutant gas and the usage ratio of the core-shell CuO@SiO2 adsorbent are: 1000 ppm: 0.2-0.3 g.

[0036] Preferably, the flow rate of the sulfur-containing pollutant gas is 30 to 40 mL / min.

[0037] Beneficial effects: The sulfur-containing pollutant gas is introduced into the reactor at a flow rate of 30 to 40 mL / min. This flow rate design optimizes the contact time between the gas and the adsorbent, thereby improving the adsorption efficiency. The reaction is carried out at room temperature and pressure, the operating conditions are simple, and there is no need for expensive equipment and complex temperature control measures, which is more in line with actual production needs. The total sulfur concentration of the sulfur-containing pollutant gas is 1000 ppm, and the amount of core-shell CuO@SiO2 adsorbent used is 0.2 to 0.3 g. This ratio setting ensures that the use of the adsorbent achieves the best effect, which can not only efficiently remove pollutants, but also help save raw material costs.

[0038] Compared with the prior art, the present invention has the following advantages and technical effects:

[0039] (1) The adsorbent of the present invention has a unique core-shell structure. The outer layer of the CuO nanocore is coated with a SiO2 shell. After calcination, the core-shell CuO@Sp·SiO2 adsorbent is obtained. The introduction of the mesoporous structure (SiO2 shell) during the synthesis process significantly increases the specific surface area of ​​the material and realizes the transformation of the pore structure from macropores (CuO core) to mesopores. It also protects the internal active sites, thereby improving its sulfur and carbon resistance, achieving the adsorption and removal of multi-component sulfur-containing pollutants, and has good application prospects.

[0040] (2) The present invention cleverly encapsulates CuO nanocores in SiO2 shells and produces core-shell CuO@Sp·SiO2 adsorbents after calcination, which breaks through the inherent structure of traditional adsorbents and utilizes the strong interaction between the adsorbent's electronic metal carrier interaction and the adsorbed species to significantly improve the desulfurization efficiency of the adsorbent.

[0041] (3) The core-shell CuO@Sp·SiO2 adsorbent prepared by the present invention has the following advantages compared with existing adsorbents for removing sulfur-containing pollutants:

[0042] 1) Simultaneous removal of multi-component sulfur-containing pollutants: The core-shell CuO@Sp·SiO2 adsorbent prepared by the present invention can simultaneously adsorb and remove multi-component sulfur-containing pollutants, including three-component, two-component, and single-component gases, at normal pressure and 25-30°C. Compared with the single gas component of traditional adsorbents, it is more in line with actual working conditions and has a wider range of applications.

[0043] 2) High activity and low energy consumption: Compared with traditional alkali metal or alkaline earth metal modified silica and alumina-based adsorbents, the core-shell CuO@Sp·SiO2 adsorbent prepared by the present invention can achieve an adsorption and removal efficiency of sulfur-containing pollutants of 100% at atmospheric pressure of 25-30°C. The required temperature and pressure are much lower than those of alumina-based adsorbents (160°C, 1.2MPa, 100% conversion) and alkali metal or alkaline earth metal modified silica adsorbents (1-5atm, 20-50°C, <100%). BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of this application. The exemplary embodiments and descriptions of this application are intended to explain this application and do not constitute an improper limitation on this application. In the accompanying drawings:

[0045] Figure 1 The adsorption activity of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 under three-component reaction gases (CH3SH, CH3SSCH3 and H2S);

[0046] Figure 2 The adsorption activity of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 under two-component reaction gases (CH3SH, CH3SSCH3);

[0047] Figure 3 The adsorption activity of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 under a single-component reaction gas (H2S);

[0048] Figure 4 This is a TEM image of the core-shell CuO@Sp·SiO2 adsorbent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0050] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.

[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0054] The present invention discloses a method for preparing a core-shell CuO@Sp·SiO2 adsorbent, comprising the following steps:

[0055] The CuO nanocores, a reducing agent, a template and a surfactant are dissolved in water, and then a silicon source is added. After stirring and reacting, a precipitate is collected (the precipitate is a core-shell CuO@Sp·SiO2), and the precipitate is calcined to remove excess template and organic matter to obtain the core-shell CuO@Sp·SiO2 adsorbent.

[0056] In some preferred embodiments, the CuO nanocore is a commercially available nano-CuO core.

[0057] In some preferred embodiments, the reducing agent comprises ethanol;

[0058] Templating agents include hexadecyltrimethylammonium bromide;

[0059] The surfactant includes triethanolamine; triethanolamine can also be used as a dissolving agent to promote the dissolution of tetraethyl orthosilicate;

[0060] Silicon sources include tetraethyl orthosilicate.

[0061] In some preferred embodiments, the stirring reaction time is 16-24 hours.

[0062] In some preferred embodiments, the mass ratio of the CuO nanocores to the silicon source is (0.05-0.3):1.

[0063] In some preferred embodiments, the average diameter of the CuO core of the finally prepared core-shell CuO@Sp·SiO2 is 51-52 nm, and the average diameter of the sphere is 137-138 nm;

[0064] The thickness of the SiO2 shell in the core-shell CuO@Sp·SiO2 catalyst is about 86nm (137-51=86).

[0065] In some preferred embodiments, the preparation method comprises the following steps:

[0066] 112-186 mg of nano-CuO cores are dispersed in a mixed solvent of deionized water and ethanol, and alternately stirred and sonicated until homogeneous. Then, 2.9-3.2 g of hexadecyltrimethylammonium bromide (CTAB) and 0.8-1.2 mL of triethanolamine are added. The mixture is stirred until uniform, and then 1.6-2.5 mL of tetraethyl orthosilicate (TEOS) is added to the solution. The solution is stirred at room temperature for 16-24 hours. The resulting solid is separated by centrifugation, washed with an acetone-ethanol co-solvent, and dried in an oven overnight. Finally, the dried material is calcined in a tube furnace at 500-600°C for 6-10 hours. After cooling to room temperature, the resulting CuO@Sp·SiO2 core-shell sphere adsorbent is obtained, with a theoretical loading of 20-30%.

[0067] In addition, the present invention also provides a core-shell CuO@Sp·SiO2 adsorbent prepared by the above preparation method.

[0068] The application of the core-shell CuO@Sp·SiO2 adsorbent in the adsorption and removal of multi-component and / or single-component sulfur-containing pollutants (H2S / CH3SH / CH3SSCH3).

[0069] In some preferred effect examples, the above core-shell CuO@Sp·SiO2 adsorbent is used in the adsorption and removal of three-component sulfur-containing gases (CH3SH, CH3SSCH3 and H2S) and two-component sulfur-containing gases (CH3SH and CH3SSCH3) as well as a single sulfur-containing gas (H2S).

[0070] A method for removing multi-component sulfur-containing pollutants by adsorption, comprising the following steps:

[0071] (1) A constant total sulfur content (1000 ppm) was maintained during the experiment and distributed among three different reaction gases. The first system contained three sulfur-containing gases: CH3SH, CH3SSCH3, and H2S.

[0072] The second system consists of two sulfur-containing gases: CH3SH and CH3SSCH3;

[0073] The third system contains only a single sulfur-containing gas, H2S.

[0074] (2) The above three gas systems were respectively introduced into a device equipped with the above core-shell CuO@Sp·SiO2 catalyst, and multi-component sulfur-containing pollutants were adsorbed and removed under the conditions of atmospheric pressure, an experimental adsorption temperature of 40°C, and a total gas flow rate of 30-40 mL / min.

[0075] Unless otherwise specified, the "room temperature" in the present invention refers to 20-30°C.

[0076] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0077] All raw materials used in the present invention were commercially available. Nano-CuO (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), cetyltrimethylammonium chloride (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), triethanolamine, and tetraethyl orthosilicate used in the following examples were all commercially available products of analytical grade and required no further purification.

[0078] The technical solution of the present invention is further illustrated by the following examples.

[0079] Example 1

[0080] A method for preparing a core-shell CuO@Sp·SiO2 adsorbent comprises the following steps:

[0081] 120 mg of nano-CuO cores were dispersed in 220 mL of a mixed solvent of deionized water and ethanol (volume ratio of ethanol to water = 1.75:1) and alternately stirred and sonicated until homogeneous. Then, 3 g of hexadecyltrimethylammonium bromide (CTAB) and 0.9 mL of triethanolamine were added. The mixture was stirred until uniform, and then 1.8 mL of tetraethyl orthosilicate (TEOS) was added to the solution. The solution was stirred at 500-600 rpm overnight at room temperature. The resulting solid was separated by centrifugation, washed with an acetone-ethanol co-solvent, and dried in an oven overnight. Finally, the dried material was calcined in a tube furnace at 600°C for 7 hours. After cooling to room temperature, the resulting CuO@Sp·SiO2 core-shell sphere adsorbent was obtained with a theoretical loading of 21%.

[0082] Figure 4 This is a TEM image of the core-shell CuO@Sp·SiO2 adsorbent prepared in Example 1 of the present invention. The calcined core-shell CuO@Sp·SiO2 adsorbent exhibits a distinct core-shell structure, with a clearly discernible interface between the core (black) and outer shell (gray). This interface demonstrates the formation of a core-shell structure. Precise measurements determined the average diameter of the spheres to be 137-138 nm, while the average diameter of the core was 51-52 nm. This indicates a shell thickness of approximately 86 nm, indicating successful adsorbent preparation.

[0083] Comparative Example 1

[0084] Preparation method of CuO / MCM-41 adsorbent (synthesized by incipient wetness impregnation method)

[0085] (1) Test the water absorption of the commercial MCM-41 carrier to determine the amount of deionized water required for impregnation;

[0086] (2) Dissolve 1.66 g of Cu(NO3)2·3H2O in deionized water and stir or ultrasonicate until completely dissolved;

[0087] (3) Adding MCM-41 carrier to the mixed solution, stirring and ultrasonicating to ensure uniform impregnation, and standing at room temperature overnight;

[0088] After drying in an oven overnight, the dried material was placed in a tube furnace and calcined at 600° C. for 7 h. After cooling to room temperature, the CuO / MCM-41 with a theoretical loading of 21% was obtained.

[0089] Comparative Example 2

[0090] Preparation method of CuO / Co·SiO2 adsorbent (synthesized by incipient wetness impregnation method)

[0091] (1) Test the water absorption rate of the purchased commercial SiO2 carrier to determine the amount of deionized water required for impregnation;

[0092] (2) Dissolve 1.66 g of Cu(NO3)2·3H2O in deionized water and stir or ultrasonicate until completely dissolved;

[0093] (3) Adding SiO2 carrier to the mixed solution, stirring and ultrasonicating to make it evenly impregnated, and letting it stand at room temperature overnight;

[0094] (4) After drying in an oven overnight, the dried material was placed in a tube furnace and calcined at 600°C for 7 h. After cooling to room temperature, the material was taken out to obtain CuO / Co·SiO2 with a theoretical loading of 21% (where "Co" represents commercially purchased material).

[0095] Comparative Example 3

[0096] 60mg of nano-CuO cores were dispersed in a mixed solvent of 220mL of deionized water and ethanol (ethanol / water volume ratio = 1.75 / 1) and alternately stirred and sonicated until uniform. Then, 3g of hexadecyltrimethylammonium bromide (CTAB) and 0.9mL of triethanolamine were added. The mixture was stirred until uniform, and then 1.8mL of tetraethyl orthosilicate (TEOS) was added to the solution. The solution was stirred at room temperature overnight, and the resulting solid was separated by centrifugation, washed with an acetone-ethanol co-solvent, and dried in an oven overnight. Finally, the dried material was placed in a tube furnace and calcined at 600℃ for 7h. After cooling to room temperature, it was removed to obtain a CuO@Sp·SiO2 core-shell sphere adsorbent with a theoretical loading of 11%.

[0097] Effect verification

[0098] Effect Example 1 (Three-component reaction gas)

[0099] The core-shell CuO@Sp·SiO2 adsorbent prepared in Example 1 was sieved to 40-60 mesh and loaded into a fixed bed reactor with an adsorbent loading mass of 0.3 g. Sulfur-containing pollutants such as CH3SH, CH3SSCH3 and H2S (wherein CH3SH:CH3SSCH3:H2S=3:2:7) with a total sulfur content of 1000 ppm were simultaneously introduced into the fixed bed reactor. The total gas flow rate was controlled to 40 mL / min, the adsorption system pressure was atmospheric pressure, and the adsorption temperature was 40°C. An activity evaluation experiment of the three-component system for adsorption removal of sulfur-containing pollutants was carried out.

[0100] Figure 1The adsorption activity of the adsorbents prepared in Example 1, Comparative Examples 1, and Comparative Examples 2 under a three-component reaction gas (CH3SH, CH3SSCH3, and H2S) is shown. As can be seen from the figure, in this three-component system, the CuO@Sp·SiO2 adsorbent in Example 1 exhibits significant desulfurization performance for CH3SH. At the initial stage of the experiment, its desulfurization activity reached 100%. Regarding the removal of CH3SSCH3, the CuO@Sp·SiO2 adsorbent can continuously and effectively adsorb CH3SSCH3, showing remarkable stability.

[0101] The activity of CuO / MCM-41 in Comparative Example 1 for CH3SH and H2S began to deactivate after the experiment began, and its activity was much lower than that of the adsorbent in Example 1; and although the CuO / MCM-41 adsorbent had the best removal activity for CH3SSCH3, its stability was lower than that of the adsorbent in Example 1.

[0102] In Comparative Example 2, the desulfurization efficiency of CuO@Co·SiO2 for CH3SH and H2S rapidly decreased after the start of the experiment; and the CuO@Co·SiO2 adsorbent exhibited a CH3SSCH3 removal effect opposite to that of Example 1. Specifically, the removal rate of CH3SSCH3 was negative at the beginning, which may be due to its lack of adsorption activity for CH3SSCH3 and the catalytic oxidation of CH3SH to CH3SSCH3. Then, its removal efficiency increased, but was still much lower than that of Example 1.

[0103] In addition, in the three-component system, the desulfurization performance of the adsorbent prepared in Comparative Example 3 for CH3SH was only 60% at the beginning of the experiment, which was a decrease of about 40% compared with the adsorbent in Example 1. At the same time, the adsorbent in Comparative Example 3 could continuously adsorb CH3SSCH3, which had the same pattern as the adsorbent in Example 1.

[0104] Effect Example 2 (Two-component reaction gas)

[0105] The difference between the experimental process of evaluating the activity of the two-component system for adsorption removal of sulfur-containing pollutants in Effect Example 2 and Effect Example 1 is that the two-component reaction gas replaces the three-component reaction gas, CH3SH and CH3SSCH3 with a total sulfur content of 1000 ppm (wherein CH3SH:CH3SSCH3=9:1).

[0106] Figure 2 The adsorption activity of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 under two-component reaction gas (CH3SH, CH3SSCH3) is shown in Table 1. Figure 2As can be seen from the figure, in the two-component system, the CuO@Sp·SiO2 adsorbent of Example 1 still exhibits a significantly high desulfurization performance for CH3SSCH3. In addition, the CuO@Sp·SiO2 adsorbent also has a significantly high desulfurization performance for CH3SH, showing 100% desulfurization activity at the beginning of the experiment.

[0107] The removal stability of CH3SSCH3 by the CuO / MCM-41 adsorbent in Comparative Example 1 was much lower than that of the adsorbent in Example 1; and the removal adsorption rate of CH3SH dropped rapidly to below 25% in the initial stage.

[0108] In comparative example 2, the desulfurization efficiency of CuO@Co·SiO2 for CH3SH drops rapidly after the start of the experiment; the removal rate of CH3SSCH3 in the initial stage is negative, similar to that in effect example 1, and its desulfurization efficiency is much lower than that of the adsorbent in example 1.

[0109] In addition, in the two-component system, the desulfurization performance of the adsorbent prepared in Comparative Example 3 for CH3SSCH3 decreased by about 35% compared with the adsorbent in Example 1. At the beginning of the experiment, the desulfurization performance of the adsorbent for CH3SH was 64%, which was far lower than the 100% in Example 1.

[0110] Effect Example 3 (Single-component hydrogen sulfide reaction gas)

[0111] Effect Example 3 The experimental process for evaluating the activity of a single-component system for the adsorption and removal of sulfur-containing pollutants is different from that of Effect Example 1 in that the single-component reaction gas is replaced by a three-component reaction gas with a total sulfur content of 1000 ppm H2S.

[0112] Figure 3 The adsorption activity of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 under a single-component reaction gas (H2S) is shown in Table 1. Figure 3 It can be seen that in the single-component system, the CuO@Sp·SiO2 adsorbent of Example 1 has a significantly high desulfurization performance for H2S, with 100% desulfurization activity at the beginning of the experiment;

[0113] The CuO / MCM-41 adsorbent of Comparative Example 1 was rapidly deactivated after the start of the experiment, and its desulfurization efficiency was much lower than that of the adsorbent of Example 1;

[0114] The H2S desulfurization efficiency of CuO@Co·SiO2 in comparative example 2 drops rapidly after the start of the experiment. When its activity drops below 20%, the desulfurization efficiency of the adsorbent in Example 1 is still 100%. The desulfurization efficiency of CuO@Co·SiO2 is much lower than that of the adsorbent in Example 1.

[0115] In addition, in the single-component system, the H2S desulfurization performance of the adsorbent prepared in Comparative Example 3 was only 70% at the beginning of the experiment, which was significantly lower than that of Example 1, with a decrease of about 30%.

[0116] The above are merely preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

Claims

1. A method for preparing a core-shell CuO@Sp·SiO2 adsorbent, characterized in that: The following steps are involved: Dissolve nano CuO, a reducing agent, a template agent and a surfactant in water, add a silicon source, stir and calcine to obtain a CuO@Sp·SiO2 adsorbent with nano CuO as the core and spherical SiO2 as the shell. Wherein, the mass ratio of the nano-CuO to the silicon source is (0.05-0.3):

1.

2. The method for preparing a core-shell CuO@Sp·SiO2 adsorbent according to claim 1, characterized in that: The reducing agent includes ethanol; The template agent includes hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride; The surfactant is one of triethanolamine or diethanolamine; The silicon source includes tetraethyl orthosilicate.

3. The method for preparing a core-shell CuO@Sp·SiO2 adsorbent according to claim 1, characterized in that: The stirring time is 16 to 24 hours.

4. The method for preparing a core-shell CuO@Sp·SiO2 adsorbent according to claim 1, characterized in that: The conditions during the calcination process are: Calcinate at 500-600℃ for 6-10h.

5. A core-shell CuO@SiO2 adsorbent, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 4.

6. The core-shell CuO@Sp·SiO2 adsorbent according to claim 5, characterized in that: The average diameter of the core in a single spherical core-shell CuO@Sp·SiO2 adsorbent is 51-52 nm, and the average diameter of a single sphere is 137-138 nm.

7. Use of a core-shell CuO@Sp·SiO2 adsorbent as claimed in claim 5 or 6 in the adsorption and removal of multi-component and / or single-component sulfur-containing pollutants.

8. The use according to claim 7, characterized in that: The multi-component sulfur-containing pollutant includes three components or two components; Among them, the three components of sulfur-containing pollutants are: CH3SH, CH3SSCH3 and H2S; The two components of sulfur-containing pollutants are: CH3SH and CH3SSCH; The single-component sulfur-containing pollutant is any one of CH3SH, CH3SSCH3 or H2S.

9. A method for removing multi-component or single-component sulfur-containing pollutants by adsorption, characterized in that: The following steps are involved: The sulfur-containing pollutant gas is introduced into a reactor containing the core-shell CuO@SiO2 adsorbent as described in claim 5 or 6, and adsorption and removal are carried out at normal temperature, pressure and room temperature.

10. A method for adsorbing and removing multi-component or single-component sulfur-containing pollutant gas according to claim 9, characterized in that: The ratio of the total sulfur concentration of the sulfur-containing pollutant gas and the amount of the core-shell CuO@SiO2 adsorbent is: 1000ppm: (0.2-0.3)g; the inlet flow rate of the sulfur-containing pollutant gas is 30-40mL / min.

Citation Information

Patent Citations

  • Preparation method of nano copper oxide @ mesoporous silica core-shell structure material

    CN105642286A

  • Regenerable system for the removal of sulfur compounds from a gas stream

    CN106102901A

  • Nano-porous copper oxide, preparation method thereof and application thereof in garbage stink

    CN111675237A

  • Egg yolk-shell nanoparticles for removal of H2S from gas stream

    CN114761520A